Detection and Differentiation of Malaysian Newcastle Disease Virus Isolates by RNA-Polymerase Chain Reaction and Cycle Sequencing - Ng, Ban Kim (1995)
This study was undertaken to develop diagnostic tests for Newcastle disease virus (NDV) based on RNApolymerase chain re action (RNA-PCR) and cycle sequencing techniques as a supplement to the presently available tests. Two RNA-PCR cycle sequencing systems each targeted at the haemagglutinin-neuraminidase (HN) and fusion (F) genes were developed. RNA-PCR amplification of a 398 base pairs (bp) HN gene fragment was performed on total RNAs extracted from infected allantoic fluid of 9 Malaysian NDV field isolates, vaccine strain V4-UPM and velogenic strain AF2240. Sequence analysis over 113 bases in the amplified fragment showed variations among these isolates/strains. However, identical sequences were obtained from some of the field isolates within a particular pathotype and these were thought to be of the same strain of NDV. RNA-PCR amplification of a 242 bp F gene fragment was performed on total RNAs which were isolated from several types of tissues (spleen, brain and lung) from six non-vaccinated chickens which were challenged with the velogenic strain AF2240. The spleen was found to have the highest number of samples positive by PCR. Spleens from uninfected chickens as well as those from vaccinated and challenged chickens which were slaughtered were all PCR negatives. The challenged virus was thought to have been neutralised by the antibodies produced by the chickens. The identity of the PCR products amplified from the spleens w'ere confirmed by cycle sequencing. Similarly, this test was also performed on RNAs from infected allantoic fluid of 11 different NDV strains/isolates. These samples were also PCR positives.